Internet connectivity disruption in Finland (Finland) - Voidly (2026)
CRITICAL severity disruption detected in Finland. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: FI-2026-0004
Keywords: internet disruption; FI; disruption; critical